How 5G-based industrial IoT is transforming human-centered smart factories: a Quality of Experience model for Operator 4.0 applications. Issue 1 (2021) - Longo, Francesco; Padovano, Antonio; Aiello, Giuseppe; Fusto, Caterina; Certa, Antonella
Abstract: As factories move towards Industry 4.0, the replacement of control communications based on Ethernet and other wired technologies with wireless becomes an imperative to fulfill the envisioned flexibility and easy reconfigurability of the production facilities. While wired connections are often unwanted for their limited flexibility and high maintenance costs, common wireless technologies in manufacturing such as Bluetooth, Wi-Fi, ZigBee, or 4G cannot fulfil the requirements of timeliness, reliability, data rates, scalability and availability of cyber-physical production systems. Today, the fifth-generation (5G) broadband cellular network technology holds the promise for an enhanced Quality of Service (QoS) and Quality of Experience (QoE) that unlock a huge amount of value and opportunity. However, at present, application of 5G wireless communication technology in the manufacturing industry is still at its infancy. In this paper, 5G is presented as a game changer for human-machine and human-robot interaction in three manufacturing use cases (i.e. uRLLC-based human-robot collaboration, eMBB-based AR-assisted operations and mMTC-based interaction with the digital twin). A QoS/QoE model is presented to drive the implementation of 5G-aided solutions for the Operator 4.0, thus maximizing the network quality and acceptance rate of digital technologies in the shop floor (that have never been widely accepted and used in practice by the industrial workforce). This paper explores how a 5G could finally provide the necessary network infrastructure for the human-machine symbiosis in the factory of the future.